Theoretizing a new sustainable business event : extension of Mair and Jago model / Norol Hamiza Zamzuria ... [et al.] - Awang, Khairil Wahidin; Abdul Aziz, Yuhanis; Samdin, Zaiton (Faculty of Business and Management, 2015)
The growth of the event sector is underpinned by the demand of organizing a business event. Thus, it leads to an increase in economic and social impact. However, the problems from the growth of this sector potentially results from the use of several event materials, transportation and infrastructure development. Organizing a green event is seen as one of the strategies to reduce the environmental impact. Therefore, the aim of this paper is to explore the issues involved throughout the process of greening an event by applying Mair and Jago Model. Semi-structured interviews were conducted with event managers from six Malaysia business event companies that encourage green practices during their event. Findings suggest that impact, initiative, support and performance motivates event organizers in organizing a green event. It has also been found that knowledge, resources and behaviour are the barriers faced by event organizers throughout the process of organizing a green event. Based on the findings it appears that two important factors have emerged from the data collection and analysis that showed a deviation from the Mair and Jago Model, namely “impact” for the motivation element and “support” for the barrier element. The main limitation of this study was the scope of the study; as it only focuses on business events. However, as the main purpose of this study is to explore the issues of organizing a green event, it has been found that there are other issues need to be explored in other contexts and geographical area. Apart from this, as this is a case study, it can only replicate according to the circumstances of this case study. However, this study can be generalized in terms of the theory that has emerged from it. It is suggested that further research should explore more issues in other contexts and geographical areas.